Phytochemical screening and enzymatic and antioxidant activities of Erythrina suberosa (Roxb) bark - Zubair Ahmed; Sohail Aziz; Muhammad Hanif; Syed Ghouse Mohiuddin; Sayed Hurmat Ali Khan; Rizwan Ahmed; Siti Maisharah Sheikh Ghadzi; Ahmad Naoras Bitar (Wolters Kluwer Medknow Publications, 2020)
Background: This study aimed to evaluate the phytochemicals screening of Erythrina suberosa (Roxb) bark and to analyze the enzymatic activities of its various organic fractions. Materials and Methods: Crude methanolic fraction of E. suberosa (Roxb) bark and its respective fractions were screened for the presence of different phytochemicals with different reagents. On the basis of increasing order of polarity, different organic solvents were used to obtain different fractions. Enzymatic studies were performed on crude methanolic extract of the plant. All the assays were performed under standard in vitro conditions. Results: The phytochemical analysis shows the presence of alkaloids, phenols, triterpenoids, phytosterols, and flavonoids. Phenolic compounds and flavonoids are the major constituents of the plant. In anticholinesterase assay, the percent inhibition of standard drug (eserine) was 91.27 ± 1.17 and the half maximal inhibitory concentration (IC50) was 0.04 ± 0.0001. For α-glucosidase inhibition, the IC50 value for Dichloromethane fraction was 8.45 ± 0.13, for Methanol fraction it was 64.24 ± 0.15, and for aqueous fraction it was 42.62 ± 0.17 as compared with standard IC50 that is 37.42 (acarbose). Furthermore, results show that all fractions have potential against anti-urease enzyme, but DCM fraction of crude aqueous extract has significant IC50 value (45.26 ± 0.13) than other fractions. Conclusion: Keeping in view all the results, it is evident that the plant can be used in future for formulating effective drugs against many ailments. Secondary metabolites and their derivatives possess different biological activities, for example, .g. flavonoids in cancer, asthma, and Alzheimer. Furthermore, the extracts of this plant can be used in their crude form, which is an addition to the complementary and alternative treatment strategies.